Linear motion control with a low-power hydraulic switching converter - Part II: Flatness-based control. (October 2015) - Kogler, Helmut; Scheidl, Rudolf
Hydraulic switching control is an opportunity for economic, robust and energy efficient hydraulic motion control. The hydraulic buck converter represents a promising concept, which meets these requirements. Part I of this publication has shown that for a convenient control performance a model-based control should be applied. In this paper a flatness-based controller for linear hydraulic motion control with a sub-kilowatt hydraulic buck converter is presented. A simple model-based on an averaging of the switching converter is employed to derive a flatness-based controller combined with a nonlinear observer to estimate all system states only from a position signal. Its performance is studied by simulations and experiments for large ramp type and sinusoidal motions of a heavy mass. Comparison of motion quality and energy consumption are made between the converter and a standard hydraulic proportional drive using a servo-valve instead of the switching converter. With this flatness-based controller a tracking performance as good as of a proportional drive can be achieved, yet at much better efficiency. Proportional control for the switching converter, however, leads to inferior results for this type of intended motions.